Model associativity alpaqueras SME supply chains to raise the level of competitiveness in the international market - Buse Thorne, Eduardo (2012)
Small and medium enterprises (SMEs) that make alpaca fiber products, require a model of partnership that enables dynamic and efficient care in the short term, demand for their goods, these requirements are the result of international treaties the country has signed. This model takes into account the particular characteristics that markets have, commons and key stakeholders, so that in this way succeeds in raising the competitiveness of domestic products in the international market and thus the development and improvement of quality of life.